Single-nucleotide promoter polymorphism alters transcription of neuronal nitric oxide synthase exon 1c in infantile hypertrophic pyloric stenosis - Saur, Dieter (National Academy of Sciences, 2004)
Infantile hypertrophic pyloric stenosis (IHPS), characterized by enlarged pyloric musculature and gastric-outlet obstruction, is associated with altered expression of neuronal nitric oxide synthase (nNOS). Here we have studied molecular mechanisms by which nNOS gene expression is altered in pyloric tissues of 16 infants with IHPS and 9 controls. A significant decreased expression of total nNOS mRNA was found by quantitative RT-PCR in IHPS after normalization against GAPDH, which predominantly affected exon 1c with a reduction of 88% compared with controls (P < 0.001). After normalization against the neuronal-specific gene PGP9.5, expression of exon 1c was still decreased (P < 0.001), whereas expression of exon 1f was increased significantly (P = 0.001), indicating a compensatory up-regulation of this nNOS mRNA variant. DNA samples of 16 IHPS patients and 81 controls were analyzed for nNOS exon 1c promoter mutations and single-nucleotide polymorphism (SNP). Sequencing of the 5′-flanking region of exon 1c revealed mutations in 3 of 16 IHPS tissues, whereas 81 controls showed the wild-type sequence exclusively. Carriers of the A allele of a previously uncharacterized nNOS exon 1c promoter SNP (-84G → A) had increased risk for development of IHPS (odds ratio, 8.0; 95% confidence interval, 2.5–25.6). Reporter gene assays revealed an unchanged promoter activity for mutations but a ≈30% decrease for the -84A SNP (P < 0.001). In summary, our findings indicate that genetic alterations in the nNOS exon 1c regulatory region influence expression of the nNOS gene and may contribute to the pathogenesis of IHPS.